ANTI-INFLAMMATORY ACTIVITIES OF TEMULAWAK, GINGER, SOYBEAN AND SHRIMP SHELL EXTRACTS IN COMBINATION COMPARED TO DICLOFENAC SODIUM - Nyoman Kertia; Deddy Nur Wachid Akhadiono; Ayu Paramaiswari; Arina Syarifa Fadlilah; Hangga Harinawantara (Acta Interna The Journal of Internal Medicine, 2011)
ABSTRACT Background: The prevalence of osteoarthritis (OA) in the community is high. This disease is the second most common cause of physical disability worldwide. Pain in OA is caused by several factors, such as inflammation. Non steroidal anti-inflammatory drugs (NSAIDs) were the most common drugs given worldwide to reduce pain in OA. NSAIDs were also associated with a high incidence of gastrointestinal side effects. An alternative to manage this problem is by using the combination of Curcuma xantorrhyza Roxb. (commonly known as temulawak) extract, ginger (Zingiber officinale) extract, soybean (Glycine max), and shrimp shell. Curcuma xantorrhyza contains curcumin which has anti-inflammatory effect by suppressing cyclo-oxygenase (COX-2) enzyme activity, suppressing lipo-oxygenase enzyme activity, and play a role as a free radical scavenger. Ginger can inhibit COX-2 activity in PGE-2 production. Shrimps shell contains glucosamine and chondroitin which can increase proteoglycan in articular chondrocytes and inhibit COX-2 synthesis. Isoflavone in soybean can inhibit articular cartilage degradation and COX-2 synthesis.Study Aims: The purpose of this study is to compare the effect of the combination to diclofenac sodium in reducing synovial fluid leukocyte count and joint pain in patients with osteoarthritis.Study Method:This study was a prospective randomized open end blinded evaluation (PROBE). Twenty one patients with knee osteoarthritis diagnosed by American College of Rheumatology criteria were included in this study. Patients were randomized into two groups to receive either diclofenac sodium 25 mg (control group) or the combination of Curcuma xantorrhyza extract 50 mg, ginger extract 100 mg, shrimp shell 100 mg, and soy bean flour 50 mg (treatment group) three times daily for 14 days. Independent t-tests and Mann-Whitney-Wilcoxon tests were used to evaluate changes between prior and post intervention.Results:  There were significantly reduction of synovial fluid leukocyte count in both control group (p=0.017) and treatment group (p=0.008) respectively.  The reduction of synovial fluid leukocyte count was not significantly different between control group and treatment group (p=0.929).  There were significant improvement of joint pain (VAS score) in both control group (p=0.012) and treatment group (p<0.001).  The reduction of VAS score was not significantly different between diclofenac group and treatment group (p=0.607).Conclution: These results indicate that the evicacy of this combiation was not significantly different with diclofenac sodium in reducing the synovial fluid leukocyte count and joint pain in patients with osteoarthritis.Keywords: osteoarthritis, Synovial fluid leukocyte count, Pain, VAS, Diclofenac sodium,Combinaion of curcuma, ginger, shrimp shell and soybean.